Mekanisme pasar dalam ekonomi Islam - Ibad, Ahmad Irsyadul; Zahra, Alvika Tanzila Azizatuz (Maliki Interdisciplinary Journal, 2024)
Islamic economics holds that since the state, the market, and the individual are all in a healthy state of equilibrium (iqtishad), there cannot be subordinates who allow one of them to supplant the other. In Islam, market freedom is a given. The techniques of production and pricing are decided by the free market; thus, there shouldn’t be any alterations that throw off the equilibrium of the market. Islam, however, permits the state to intervene in the market to return it to normal since it is rare to find a market that operates on its own decently (fairly), and because market distortions frequently happen and can hurt the participants. The capitalist, the infrastructural authority, and the information owner have all unilaterally controlled the market as a result of it being let to operate unchecked (laissez faire). Another issue that cannot be resolved by the market is information asymmetry. In Islam, the state plays a similar function to the market in that it is responsible for overseeing and regulating the economy as well as making sure there is perfect market competition, fair access to information, and economic justice. The hadith of Rasululllah Saw can be used to reference the idea of market foodism in Islam. Islam has developed the idea of market mechanisms far earlier than the West. Beginning with Abu Yusuf, Al-Ghazali, Ibn Taymiyah, Ibn Khaldun, and other academics throughout history, the idea of market processes in Islam was further explored scientifically. These academics have covered the idea of market processes in great detail. The importance of supply and demand has been debated. Their research has also touched on market influencers. The forces of supply and demand control pricing in an Islamic economy. The government may enter the market if there is a market distortion. However, Islamic economics opposes excessive government regulation that interferes with the free operation of the market to produce competitive pricing.